Rare renal manifestation of plasma cell disorder - Shahar, Shamira; Lim, Christopher Thiam Seong; Mohamad, Haidi; Abd Ghani, Fauzah; Bak, Leong Goh (Malaysian Society of Nephrology, 2024)
CASE PRESENTATION: A 56 year old lady presented with 2 weeks history of nausea, vomiting, and unintentional weight loss, with reduced eff 01t tolerance. She has underlying type 2 diabetes mellitus, and hype1tension. On examination, blood pressure was 140 / 80mmhg, pallor conjunctivae, and other physical examination was normal. Her investigations showed creatinine of 1214 umol/L, urea 24.3 mmol/L, eGFR of 2 ml/min/1.73m2, albumin 35 g/L, total protein 71g/L, globulin 34g/L, albumin /globulin ratio 1.08, haemoglobin 6.8 g/dl, platelet 312x 103/uL, total white cell 7.97 x 10 9/L, calcium 2.44 mmol/L, phosphate 2 mmol/L, and e1ythrocyte sedimentation rate (ESR) 100 mm/hr. Urine microscopy shows 1 + protein, no REC presence and urine protein creatinine index of 12.9g/day. Immunology screening revealed nonnal ANA, C3, C4, and ANCA. Kidney ultrasound shows a left kidney size of 10.3cm, and right kidney of 11.7cm with preserved cmticomedullary differentiation bilaterally. She was initially diagnosed with ESKD, and long-tenn kidney replacement therapy was planned for her.